Association Between Sleep Problems and Perceived Cognitive Dysfunction Over 12 Months in Individuals with Multiple Sclerosis. Issue 1 (2nd January 2018) - Hughes, Abbey J.; Turner, Aaron P.; Alschuler, Kevin N.; Atkins, David C.; Beier, Meghan; Amtmann, Dagmar; Ehde, Dawn M.
Abstract : Sleep problems are highly prevalent among individuals with multiple sclerosis (MS); however, the relationship between sleep problems and cognitive dysfunction is poorly understood in this population. In the present study, 163 individuals with MS and depression, fatigue, or pain completed self-report measures of sleep, cognitive dysfunction, and relevant demographic and clinical characteristics (e.g., disability severity, depressive symptomatology, pain intensity, fatigue impact) at four time points over 12 months. Mixed-effects regression demonstrated that poorer sleep was independently associated with worse perceived cognitive dysfunction ( β = –0.05, p = .001), beyond the influence of depressive symptomatology. Fatigue impact was found to partially mediate this relationship. Results suggest that for individuals with MS and depression, fatigue, or pain, self-reported sleep problems are related to perceived cognitive dysfunction, and that fatigue impact accounts for part of this relationship.